Advertisement Remove all ads

Evaluate the following : ∫01logx1-x2⋅dx - Mathematics and Statistics

Sum

Evaluate the following : `int_0^1 (logx)/sqrt(1 - x^2)*dx`

Advertisement Remove all ads

Solution

Let I = `int_0^1 (logx)/sqrt(1 - x^2)*dx`

Put x = sin θ
∴ dx = cos θ dθ
and
`sqrt(1 - x^2) = sqrt(1 - sin^2 theta) = sqrt(cos^2 theta)` = cos θ

When x = 0, sin θ = 0  ∴ θ = 0
When x = 1, sin θ = 1  ∴ θ = `pi/(2)`

∴ I = `int_0^(pi/2) log sin theta *d theta`

Using the property, `int_0^(2a) f(x)*dx = int_0^(a)[f(x) + f(2a - x)]*dx`, we get

I = `int_0^(pi/4) [log sin theta + log sin (pi/2 - theta)]*d theta`

= `int_0^(pi/4) (log sin theta + log cos theta)* d theta`

= `int_0^(pi/4) log sin theta cos theta* d theta`

= `int_0^(pi/4) log((2 sin theta cos theta)/2)*d theta`

= `int_0^(pi/4) (log sin 2 theta - log 2)*d theta`

= `int_0^(pi/4) log sin 2 theta*d theta - int_0^(pi/4) log 2* d theta`

= I1 – I2                                                  ...(Say)

I2 = `int_0^(pi/4) log 2* d theta`

= `log 2 int_0^(pi/4) 1*d theta`

= `log 2 [theta]_0^(pi/4)`

= `(log 2)[pi/4 - 0]`

= `pi/(4) log 2`

I1 = `int_0^(pi/4) log sin 2 theta * d theta`

Put 2θ = t. 

Then dθ= `dt/(2)`

When θ = 0, t = 0

When θ = `pi/(4), t = 2(pi/4) = pi/(2)`

∴ I1 = `int_0^(pi/2) log sin t xx dt/(2)`

= `(1)/(2) int_0^(pi/2) log sin theta* d theta`

= `(1)/(2)"I"     ...[ because int_a^b f(x)*dx = int_a^b f(t)*dt]`

∴ I = `(1)/(2) "I" - pi/(4)log 2`

∴ `(1)/(2)"I" = - pi/(4) log 2`

∴ I = `- pi/(2) log 2`

= `pi/(2) log (1/2)`.

  Is there an error in this question or solution?
Advertisement Remove all ads

APPEARS IN

Advertisement Remove all ads
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×